Phosphodiesterase 4 inhibitors attenuate virus‐induced activation of eosinophils from asthmatics without affecting virus binding - Yanaika Shari Sabogal Piñeros; Tamara Dekker; Barbara Smids; Christof J. Majoor; Lara Ravanetti; Gino Villetti; Maurizio Civelli; Fabrizio Facchinetti; René Lutter (Wiley, 2020)
Abstract Acute respiratory virus infections, such as influenza and RSV, are predominant causes of asthma exacerbations. Eosinophils act as a double‐edged sword in exacerbations in that they are activated by viral infections but also can capture and inactivate respiratory viruses. Phosphodiesterase type 4 (PDE4) is abundantly expressed by eosinophils and has been implicated in their activation. This exploratory study aims to determine whether these opposing roles of eosinophils activation of eosinophils upon interaction with virus can be modulated by selective PDE4 inhibitors and whether eosinophils from healthy, moderate and severe asthmatic subjects respond differently. Eosinophils were purified by negative selection from blood and subsequently exposed to RSV or influenza. Prior to exposure to virus, eosinophils were treated with vehicle or selective PDE4 inhibitors CHF6001 and GSK256066. After 18 hours of exposure, influenza, but not RSV, increased CD69 and CD63 expression by eosinophils from each group, which were inhibited by PDE4 inhibitors. ECP release, although not stimulated by virus, was also attenuated by PDE4 inhibitors. Eosinophils showed an increased Nox2 activity upon virus exposure, which was less pronounced in eosinophils derived from mild and severe asthmatics and was counteracted by PDE4 inhibitors. PDE4 inhibitors had no effect on binding of virus by eosinophils from each group. Our data indicate that PDE4 inhibitors can attenuate eosinophil activation, without affecting virus binding. By attenuating virus‐induced responses, PDE4 inhibitors may mitigate virus‐induced asthma exacerbations.